KINETOPROPHYLAXIS OF OSTEOPOROSIS IN ELDERLY PEOPLE IN THE POST COVID PERIOD - Zavalişca Aurica; Zavalişca Aurica (Sport şi Societate)
Globally, there is a noticeable demographic increase in the elderly population, an inevitable reality. The introduction of restrictionsduring the COVID-19 pandemic had profound effects on global health, both directly through the sequelae caused by the infection and indirectly, including the relative neglect of chronic disease management. Among the most common chronic conditions affectingindividuals aged over 60 is osteoporosis. This condition is characterized by bone fragility, associated with a significantly increased risk of falls and fractures, leading to physical weakness and a heightened risk of mortality. The treatment of osteoporosis extends beyond medication and includes physical and rehabilitation interventions. Kinesiotherapy is an essential non-pharmacological tool for maintaining and improving the physical functionality of individuals affected by this condition.Kinetic prophylaxis refers to the prevention and reduction of the risk of musculoskeletal deterioration through adapted and corrective physical exercises, which is particularly important in the post-pandemic context of COVID-19.